LECTURERS’ POLITENESS STRATEGIES AND STUDENTS’ COMPLIANCE IN ENGLISH FOR FOREIGN LANGUAGE (EFL) CLASS - Fitriyah Fitriyah; Nurmala Dewi; Octa Pratama Putra; Meiva Eka Sri Sulistyawati (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
The aim of this study is to find out the politeness strategies used by the teachers and students, and how the politeness affects to the student’s compliance. The focus is on directive and expressive speech acts in English for Foreign Language (EFL) Class. The subjects of this study were three lecturers and the students of three English classes. In data collecting procedure, the researcher used observation techniques. The observation was used to record the audio and video of teaching and learning process from the beginning until the end of the class. The audio-record of teaching and learning process will be transcribed into convention transcript, and then the transcript will be selected and classified into ten maxims in doing politeness strategies.  The analytical part adopts the viewpoints of Leech’s (2014) “The Components Maxims of the General Strategy of Politeness”. In the data analysis, it is found that 1) the teachers used ten maxims in their communication to the students. They are tact maxim, generosity maxim, approbation maxim agreement maxim, Obligation (of S to O) maxim, sympathy maxim, modest maxim, Obligation (of O to S) maxim, Opinion reticence maxim, and feeling reticence maxim. 2) The lecturers dominantly used tact maxim in their directive speech acts to the students. The last part of this paper aims at summarizing the implications that this paper, its theoretical summary, and its research, have for teaching English as a Foreign Language (EFL) class.